2017
DOI: 10.18203/2319-2003.ijbcp20175209
|View full text |Cite
|
Sign up to set email alerts
|

Geriatric prescription analysis with respect to “STOPP” and “START” criteria: a descriptive study in the Indian scenario

Abstract: Background: Patients; sixty-five years of age and above, are a special risk group as far as drug prescribing is concerned. Prescription irregularities in such patients may be hazardous. STOPP/START criteria are considered as the most up to-date set of explicit criteria for evaluating geriatric prescriptions. To analyse geriatric prescriptions in a tertiary care centre with respect to STOPP/START criteria and WHO core drug prescribing indicators so as to get an idea of pattern of drug prescription in geriatric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 11 publications
3
0
0
Order By: Relevance
“…The latest version 2 comprises of 80 indicators pertaining primarily to important drug-drug and drug-disease interactions and therapeutic duplication, arranged according to relevant physiological systems for ease of use. 8 In the present study, out of 60 prescriptions PIM was observed more in males which is comparable to the study done by Nagendra Vishwas et al 7 and PIM was observed more common in age group of 65-75 years (Figure 1) with mean age of 73.42 years which is like the study done by Kanagasanthosh et al 9 Polypharmacy defined as the regular use of five or more medications, is common among older adults. 10 It is an area of concern for elderly because of several reasons.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The latest version 2 comprises of 80 indicators pertaining primarily to important drug-drug and drug-disease interactions and therapeutic duplication, arranged according to relevant physiological systems for ease of use. 8 In the present study, out of 60 prescriptions PIM was observed more in males which is comparable to the study done by Nagendra Vishwas et al 7 and PIM was observed more common in age group of 65-75 years (Figure 1) with mean age of 73.42 years which is like the study done by Kanagasanthosh et al 9 Polypharmacy defined as the regular use of five or more medications, is common among older adults. 10 It is an area of concern for elderly because of several reasons.…”
Section: Discussionsupporting
confidence: 89%
“…The global rate of PIM ranges from 12% to 40% and in our study rate of PIM prescriptions is 35% which is similar to study done by Gallagher et al 14 Among Indian studies, our rate of PIM was higher than the study done by Vishwas et al 7 (13.3%) and Murthy et al (21.01%). 8. The most common PIM is aspirin (n=6) and comparable results were seen in the studies done by Murthy et al 8 and Mathur et al 15 In the above studies, the most common diseases found in elderly patients are IHD, CVA, RHD and angina for which Aspirin is prescribed usually by physicians.…”
Section: (95%)supporting
confidence: 72%
See 1 more Smart Citation